Asteroid families interacting with secular resonances - Carruba, Valerio [UNESP] (Elsevier, 2024)
Asteroid families form from collisions or fissions, and their initial dispersion is due to unknown ejection velocity fields. The asteroids' orbits may change due to various factors, such as gravitational effects (e.g., mean-motion, secular resonances, close encounters with massive asteroids and planets) and nongravitational effects (e.g., the Yarkovsky and Yorp forces). Secular resonances occur when there is a commensurability between the precession frequencies of an asteroid and a planet. For families interacting with secular resonances, conserved quantities of secular dynamics can provide information on the original ejection velocity field, which is not typically available for other asteroid groups. Here we will investigate how ML and AI can improve the process of recognizing asteroids in secular resonant configurations and how this can be used to improve our knowledge of asteroid families' formation.
Keywords: Data bases; Minor planets, asteroids: general; Minor planets, asteroids: individual